Water Pollution and Its Impact on Environment of Society - Thyagaraju, N. (International Research Journal of Management, IT & Social Sciences, 2016)
The present seminar paper mainly highlightÂ  the concept ofÂ  water pollution, causes of water pollution,Â  Its Effects, Elements ofÂ  pollutants, MethodsÂ  used to prevent the water pollution in environmentÂ  and the mandatory initiatives taken by the concerned authorities for prevention ofÂ  water pollution. WaterÂ Â  is essential for survival of all living organisms on the earth. Thus for human beings and plants to survive on land, water should be easily accessible. The term âPollutionâ is generally refers to addition of any foreign body either living or non â living or deletion of anything that naturally exists. The basic Sources of Water pollution causes due to Culmination into lakes, rivers, ponds, seas, oceans etc. Domestic drainage and sanitary waste, Industrial drainage and sewage, Industrial waste from factories, Dumping of domestic garbage, Immersion of Idols made of plaster of Paris, Excess use of Insecticides , pesticides, fungicides, Chemical fertilizers, Soil erosion during heavy rains and floods, Natural disasters, tsunami etc. General pollutantsÂ  which are also caused for water pollutionÂ  which include Organic, Inorganic, and Biological entities, Insecticides, Pesticides, Disinfectants ,Detergents, Industrial solvents, Acids, Ammonia fertilizers, heavy metals, Harmful bacteria, Virus, Micro âOrganisms and worms, Toxic chemicals. Agricultural lands become infertile and thereby production also drops, Spread of epidemic diseases like Cholera, Dysentery, Typhoid, Diarrhea, Hepatitis, Jaundice etc. TheÂ  basic responsibility of the Government, NGOs, National Pioneer scientific Research Institutions may conductÂ  research oriented programs on control of water pollution by createÂ  awareness among the public through mass media and Environmental Education on recycling units,Â  andÂ  water treatment plants must be established both at domestic levels and Industry levels, Every citizen must feel responsible to control water pollution. There have been many water pollution prevention acts that have been set up by the governments of the world. But these are not enough for permanent water pollution solutions. Each of us needs to take up the responsibility and do something at an everyday at individual level. Otherwise we canât survive in a society forever in a future.Â